Where do patients treated for oral cancer die? A 20-year cohort study 1992-2011. Issue 10 (December 2015) - Kamisetty, A.; Magennis, P.; Mayland, C.; Jack, B.; Lowe, D.; Rogers, S.N.
Abstract: Of 1290 consecutive patients treated between 1992 and 2011 for primary squamous cell carcinoma of the oral cavity at a regional centre, 750 had died by August 2013. About half of them (n = 373) died in hospital, 113 (15%) in a hospice, 180 (24%) at home, 57 (8%) in a care home, and 22 (3%) elsewhere. Cancer was the underlying cause of death in 64%, and of them, 56% were oral cancers. The place of death was strongly associated with the age at death and cancer being the underlying cause. The percentage of people who died from cancer at home or in a hospice rose over time across all age groups and, from 2010, accounted for two-thirds. In contrast, less than 1 in 5 who did not die from cancer, died at home or in a hospice, and in this there has been no discernible change over the last 20 years. The percentage of deaths from cancer in hospital and hospice ranged from 32%-38% and 20%-29%, respectively, across age groups. An increase in the number of deaths from cancer in care homes in those aged 75 years and over was mirrored by fewer at home. Most of those who did not die from cancer, died in hospital, two-thirds were under 65 years, 85% were aged 65-84, and 56% were older. This was mirrored by fewer deaths at home in those under 85 and more in care homes in those over 75. In conclusion, our findings suggest that patients' preferences not to die in hospital are being realised. However, at the end of their lives, patients and their carers need more support at home, and more research is required.